(untitled) (Archives of Criminology, 2008)
The text analyses the punishability of violating the right to freedom of speech in the light of rulings from the Constitutional Tribunal. The author presents an in-depth analysis of two rulings – from 30 October 2006 and from 12 May 2008 – in which the Constitutional Tribunal judged that qualifying slander as a criminal act is appropriate to the constitutional solutions, referring to the criminal law protection of the honour and dignity of every human being. Among the arguments cited by Andzrej Zoll in favour of such a thesis is the view that freedom of speech should be treated as secondary when colliding with an individual’s right to dignity and privacy. The article also sets out the conditions for excluding the punishability of slander, as well as the liability for slander of persons who perform public functions. In conclusion, the author stresses that the differentiation of the conditions of punishability for slander depending on the specific conduct or the person violating this right is not justified in the current situation from the criminal/political point of view, thus suggesting necessary changes to Article 213 of the Penal Code.